2015
DOI: 10.1080/00218464.2015.1115740
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Model Validation of the Shear Strength of Hybrid Interfaces up to Complete Failure

Abstract: The paper experimentally investigates hybrid interfaces pressure-reinforced and bonded with anaerobic adhesive. While their static strength has been deeply investigated, their behavior up to complete failure lacks of a constitutive model. This work aims to assess the applicability of a simple model involving a cohesive law and a pure friction law, in order to describe the interface behavior up to complete failure under different contact pressure levels. A systematic experimental campaign investigates the shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The comparison between the micromechanical model prediction (Equation (1), according to the coefficients in Table 3) and the literature data shows good agreement, specifically with the data from Dragoni and Mauri [2]. With regard to Loctite 243, Figure 7 highlights that the micromechanical model prediction has a slightly lower slope than the data from Dragoni and Mauri [2], while a more significant difference appears between the micromechanical model prediction and the data from Castagnetti and Dragoni [40,42]. Specifically, the micromechanical model tends to overestimate the response at low contact pressure and underestimate it at high contact pressure.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The comparison between the micromechanical model prediction (Equation (1), according to the coefficients in Table 3) and the literature data shows good agreement, specifically with the data from Dragoni and Mauri [2]. With regard to Loctite 243, Figure 7 highlights that the micromechanical model prediction has a slightly lower slope than the data from Dragoni and Mauri [2], while a more significant difference appears between the micromechanical model prediction and the data from Castagnetti and Dragoni [40,42]. Specifically, the micromechanical model tends to overestimate the response at low contact pressure and underestimate it at high contact pressure.…”
Section: Discussionmentioning
confidence: 56%
“…More recent experimental and numerical investigations by Castagnetti et al [39][40][41][42] preliminarily confirmed the applicability of this model.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations